Factors associated with excessive screen time usage among preschool children and risk for behavior problems - Musa, Husna; Abdul Rashid, Aneesa; Mohamed Sadik, Sultan Farvin; Goh, Jun Xi; Kesavan, Geeta Vaani; Nasrudin, Nurdiyana (Malaysian Paediatrics Association (MPA), 2022)
Introduction: Children spend a significant amount of screen time despite recommendations by the relevant bodies. Increased screen time in young children has been linked to an increased risk for behaviour issues. This study aims to determine behaviour problems and factors associated with excessive screen time usage among preschool children. Methods: A cross-sectional study was conducted among the parents of children aged 18-60 months in local parenting Facebook groups. Parents responded to an online questionnaire and Preschool Pediatric Symptom Checklist (PPSC) was used to screen risk for behaviour problems. Results: Over two-thirds (77%) of children spent more than one hour of screen time daily. There were significant associations between more than 1 hour of screen time daily and age ≥ 2 years old (OR 1.045, 95% CI 1.021 to 1.070), lesser among females (OR 0.345, 95% CI 0.178 to 0.671) and without gadget ownership (OR 0.74, 95% CI 0.010 to 0.565). Most children had PPSC total scores of less than 9 (75.8%) and there were no significant associations between excessive daily screen time usage with risks for behaviour problems among preschoolers in our study (p= 0.324). Conclusion: We report factors associated with excessive screen time to be; the age of more than 2 years old, the male gender, and children with gadget ownership. We found no significant association with risk for behaviour problems. Longitudinal studies are recommended to investigate the causal relationship between the effects of screen time on children's behaviour.